2021
DOI: 10.1038/s41467-021-26563-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable separation of gold by selective precipitation using a simple and recyclable diamide

Abstract: The efficient separation of metals from ores and secondary sources such as electronic waste is necessary to realising circularity in metal supply. Precipitation processes are increasingly popular and are reliant on designing and understanding chemical recognition to achieve selectivity. Here we show that a simple tertiary diamide precipitates gold selectively from aqueous acidic solutions, including from aqua regia solutions of electronic waste. The X-ray crystal structure of the precipitate displays an infini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 56 publications
0
62
0
Order By: Relevance
“…The gold extraction behaviour of these materials is mainly contributed by the immobilization of gold ions with the intrinsic porosity and the chemical reduction of the gold ion by the added functional groups. The other set of gold adsorbents, for example, two-dimensional molybdenum disulphide [16][17][18] , amyloid 19,20 , cyclodextrin 21 and diamide 22 , instead of relying on the porosity of the adsorbents, their efficient gold extraction is accounted to the chemical reduction of gold ions to Au 0 by photoreduction or the functional groups, and precipitation of gold ions with the adsorbents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gold extraction behaviour of these materials is mainly contributed by the immobilization of gold ions with the intrinsic porosity and the chemical reduction of the gold ion by the added functional groups. The other set of gold adsorbents, for example, two-dimensional molybdenum disulphide [16][17][18] , amyloid 19,20 , cyclodextrin 21 and diamide 22 , instead of relying on the porosity of the adsorbents, their efficient gold extraction is accounted to the chemical reduction of gold ions to Au 0 by photoreduction or the functional groups, and precipitation of gold ions with the adsorbents.…”
mentioning
confidence: 99%
“…These gold adsorbents exhibit a high gold extraction capacity at a gold concentration from 500 ppm-3000 ppm [12][13][14][15][16][17][18][19][20][21][22] , but this capacity decreases to less than 250 mg/g at a gold concentration range relevant to e-waste recycling, specifically, from ppb level to tens of ppm 4,12,19 . Furthermore, as the e-waste contains complex co-existing metal elements, the practical gold extraction process often requires good extraction selectivity to gold, so that separation of co-existing elements from the extracted gold can be avoided, achieving a high resource-and energy-efficiency for gold recycling.…”
mentioning
confidence: 99%
“…It can be seen from the figure that when the pH value is 5.0, the adsorption capacity of the CNC-P aerogel material is the largest, which corresponds to the lowest pH point of the material zeta potential, while the lowest pH value of the CNC-P-PNIPAM zeta potential is 6.0. 32 Here, it is shown that the adsorption capacity is the largest when the pH is 7.0, but the difference is very small when the pH is 6.0. This may be because PNIPAM is wrapped around the rod-shaped CNC surface, resulting in the surface charge being not completely exposed to the outside, so there is a deviation in the zeta potential test.…”
Section: Resultsmentioning
confidence: 84%
“…This rationalization is consistent with a recently reported X-ray structure of HAuCl 4 mixed with an aryl tertiary amide; the tecton structure lacked NH residues and there were no close contacts between the Au center and the aryl π-electrons. 51…”
Section: Resultsmentioning
confidence: 99%